2018
DOI: 10.1111/scs.12617
|View full text |Cite
|
Sign up to set email alerts
|

Access to a school health nurse and adolescent health needs in the universal school health service in Finland

Abstract: Universal school health services are expected to offer similar, needs‐based services to all students across schools, service providers and students’ socio‐economic statuses and health needs. This study investigates access to school health nurses in Finland. The objectives were to study the differences in access to school health nurse between service providers, schools, students’ characteristics and school health nurse resources. Access was examined through a nationwide School Health Promotion study, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
2
12
0
8
Order By: Relevance
“…In this study, the adolescents who perceived need for the services were likely to access AFHS, and the same thing happened in South Ethiopia (Cherie, Tura and Teklehaymanot, 2015). In Finland, adolescents who perceived need for school health nurses likely reported difficulties in accessing the service (Kivimäki et al, 2019). Adolescents who need for support would seek for the service if the AFHS available in their community met their needs (Godia et al, 2014).…”
Section: Resultsmentioning
confidence: 57%
“…In this study, the adolescents who perceived need for the services were likely to access AFHS, and the same thing happened in South Ethiopia (Cherie, Tura and Teklehaymanot, 2015). In Finland, adolescents who perceived need for school health nurses likely reported difficulties in accessing the service (Kivimäki et al, 2019). Adolescents who need for support would seek for the service if the AFHS available in their community met their needs (Godia et al, 2014).…”
Section: Resultsmentioning
confidence: 57%
“…However, in smaller schools they are only present part of the week. Still, Kivimäki et al (2019) found that youth generally reported that accessing their school nurse was easy, even though this varied between the schools [46]. The open-door policy of school nurses is important for students, as they are often the only school health professionals students can go to without a scheduled appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Access to health care is also vital in promoting equity in health [ 42 ]. Still, being a child of foreign origin is related to having a higher risk of experiencing difficulties in accessing a school nurse [ 43 ], and they also report difficulties in keeping appointments [ 11 ]. However, that the school nurses in this study describe availability as important for children of foreign origin suggests that these school nurses might be aware of the impact that availability and access have on these children’s participation in health visits and also on promoting equity in health.…”
Section: Discussionmentioning
confidence: 99%